Penentuan Rock Region berdasarkan Porositas dan Permebilitas Batuan dalam Simulasi Reservoir Migas - Yunita, Lia (Retii, 2024)
Before carrying out a reservoir simulation, porosity and permeability analysis is very important to understand the physical characteristics of the reservoir rock. Determination of these parameters helps identify the production capacity and fluid distribution in the reservoir. Correlation of core data with log data and stratigraphic simulations can provide more accurate predictions about the distribution of porosity and permeability in heterogeneous fields. Core data obtained through SCAL (Special Core Analysis) and RCAL (Routune Core Analysis) is processed into rock regions to group good and bad rock characteristics. The aim of this research is to determine rock regions based on rock permeability porosity. The method used with SCAL and RCAL analysis includes porosity, core depth permeability. After that, determine the FZI (Flow Zone Index) value obtained from the RQI (Reservoir Rock Quality Index) data divided by the NPI (Normalized Porosity Index). Then find the cumulative probability value by dividing the core sample number by the total sample number. The RQI value is obtained through permability and effective porosity data, while the NPI is obtained through porosity data. The results of research on the "ZN" formation obtained plotting between the porosity and permeability of rocks which have six rock regions based on porosity and permeability data obtained through SCAL and RCAL